On the discovery of a cave lion from the Malyi Anyui River (Chukotka, Russia). (1st June 2015) - Kirillova, I.V.; Tiunov, A.V.; Levchenko, V.A.; Chernova, O.F.; Yudin, V.G.; Bertuch, F.; Shidlovskiy, F.K.
Abstract: An incomplete postcranial skeleton (67 elements) of a cave lion, a lower jaw and a bundle of fine yellowish hair were found by a local resident in 2008 and 2009 washed out from the perennially frozen Pleistocene sediments in the lower reaches of the Malyi Anyui River (western Chukotka). This is the first skeleton of a cave lion ( Panthera spelaea Goldfuss) to be found in Russia. The bone sizes are similar to finds of cave lion bones known from N–E Russia, but larger than East Beringian and smaller than West European ones. The remains have been studied using a variety of methods, including morphology, morphometry, SEM-examination, AMS-dating, and isotopic study, which included examination of over 100 samples of various members of the mammoth faunal assemblage (mammoth, wooly rhinoceros, bison, horse, bear, etc.). The results showed that the northeastern Asian cave lion hunted mainly bison and horses, but not reindeer, unlike its Western Europe counterpart. Bone and claw sheath dating showed an unexpectedly old geochronological age of over 61, 000 years (OZQ290, OZQ291), while the hair was dated 28, 690 ± 130 (OZQ292), which makes its affinity with the same individual as the skeleton questionable. Further studies to investigate possible unremoved contamination and obtain more reliable date are planned. Highlights: The study of a cave lion skeleton (incomplete) from West Chukotka is presented. The find included skin derivatives – cornified claw sheath and possibly hair. Comparison is done with finds from Russia, Western Europe and North America. Stable isotopes are analyzed together with other species of mammoth fauna complex. Results of radiocarbon dating of bones and skin derivatives are shown and discussed.